Karakteristik mutu organoleptik yogurt susu kambing etawa dengan variasi konsentrasi ekstrak bunga telang dan lama fermentasi: Organoleptic quality of etawa goat milk yoghurt with varying concentrations of butterfly pea extract dan fermentation durations - Pramitha, Asti Rizkiana; Handarini, Kejora; Ningtyas, Rosidah Wahyu; Mekasari, Firsta Koesdyah; Saraswati, Exist (TEKNOLOGI PANGAN : Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2025)
Etawa goat milk is a nutritious, easily digestible, dan hypoallergenic alternative to cow's milk. However, goat milk yogurt often possesses a distinctive aroma that is less preferred by consumers. The addition of butterfly pea flower (Clitoria ternatea) extract, which contains anthocyanins dan other bioactive compounds, is expected to improve the sensory quality of the yogurt. Furthermore, fermentation time also influences the texture, taste, dan aroma of the final product. This study aims to evaluate the effect of combining different concentrations of butterfly pea flower extract dan fermentation durations on the organoleptic quality of Etawa goat milk yogurt. A two-factor Completely Randomized Design (CRD) was applied, involving variations in extract concentration dan fermentation time. Organoleptic evaluation was conducted for color, aroma, taste, dan texture attributes with the participation of trained panelists.The results showed that the combination of extract concentration dan fermentation time significantly affected the organoleptic properties of the yogurt. Treatment B3T3 (3% extract, 12-hour fermentation) yielded the highest scores for all sensory attributes. The improvements were attributed to anthocyanin stability, volatile compound formation, dan protein aggregation during fermentation.  The B3T3 treatment produced yogurt with the best sensory characteristics dan strong potential for consumer acceptance as a functional goat milk-based product enriched with butterfly pea flower.